Smart aquaculture system: internet of things-based contextual e-service for sustainable aquafarming - Md Abdullah Al Rahib; Md Redwan Hussain; Md. Zubayer Chowdhury; Jarin Tias Meraj; Abdus Sattar (Bulletin of Electrical Engineering and Informatics, 2026)
A creative and contextual e-service for aquaculture system is developed to handle threats that climate change poses to global ecology and sustainable aquaculture. Therefore,"ICTization framework model," is based on capacity, connectivity, and context across three layers—core, and management, and distribution— has served as the study's guide. These layers support elements of centralization, decentralization, and parallelization hence reduce misconceptions about infrastructure, development, and communication. It incorporates a four-tier conceptual framework for an e-service system based on the internet of things (IoT) that is aimed at appropriately collect and manage environmental data in real time. Each tier of the framework is further elaborated for e-services using contextual information with existing infrastructure preserved while improving synchronization of data, administration, and services. It is able to predict and respond to variations in the quality, temperature, and other vital parameters of the water. The architecture realizes aquaculture as a service by orchestrating all the stakeholders – farmers, researchers, and network operators. E-service based system shall include remote monitoring, automated feeding and water quality assessment in real-time which will significantly improve efficiency reduce cost and increase income. Moreover, improved resource efficiency and less ecological impact made possible through the proposed conceptual framework enables sustainable aquaculture practices.